Optimalisasi Kapasitas Pelayanan di Jemaat Semau Utara, Pulau Semau - Arly Elizabeth Maria de Haan; Mefibosed Radjah Pono (Yayasan Sumber Daya Manusia Cerdas, 2024)
The community service activity at the Congregation of Semau Utara aims to enhance the capacity of its service participants, focusing on structuring worship services, sermons, and understanding congregational hymns. Through lectures and training sessions, 22 church councils engage in the development process. They are provided with opportunities to directly apply the learned material in practical contexts, enabling a deeper understanding. The results indicate a significant improvement in understanding and skills in structuring worship services and sermons that are more aligned with the needs and context of the congregation. This developmental process not only reinforces the congregation's worship experience but also enhances the relevance and quality of messages delivered during worship. Thus, this activity aids service participants in expanding their theological insights and equips them with better tools to meet the spiritual and practical needs of the congregation. Overall, this developmental activity serves as a crucial step in strengthening the capacity of service participants and empowering the congregation to become more theologically independent.